Perlindungan Hukum terhadap Konsumen atas Kelalaian Perusahaan Ekspeditur Berdasarkan Undang-Undang Perlindungan Konsumen - maulitha Haliza (Jurnal Hukum Lex Generalis, 2026)
The growth of digital transactions has increased reliance on freight forwarding services and consumer loss risks when goods are lost, damaged, delayed, or not delivered. This article analyzes freight forwarders' liability and legal protection mechanisms under Law Number 8 of 1999 concerning Consumer Protection. Using a normative juridical method, the study shows that freight forwarders must compensate consumers when loss results from fault, negligence, or failure to meet service standards. Consumers may file internal complaints, seek settlement through BPSK, or bring claims before the court.